ARVIN converter: a bidirectional DC/DC converter for grid-connected G2V/V2G energy storage and electrification approaches - Ertekin, Davut (Springer, 2024)
Bidirectional DC-DC converters play a crucial role in enabling the transfer of energy between low-voltage and high-voltage sides, a fundamental requirement in applications like vehicle-to-grid and grid-to-vehicle scenarios. The motivation behind the application of common ground converters is the quest for enhanced reliability and safety while also seeking to prevent electromagnetic interferences and address the issue of dvdt\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\frac{{\text{d}}v}{{\text{d}}t}$$\end{document} between the input and output sides. This paper introduces an enhanced SEPIC converter with a common ground configuration, incorporating a quadratic switched-inductor cell. This innovative design allows for both voltage step-up and step-down operations in both directions of energy flow. The converter exhibits substantial gains and efficiency. To validate the theoretical findings, a 300W laboratory prototype of the converter was constructed and tested. Control and switching operations are managed by a DSP-based microcontroller operating at a sampling speed of 80 Mb/s, utilizing a fuzzy logic control technique. The Arvin converter, as suggested, offers numerous advantages that can be encapsulated as follows: It introduces a common ground-based high-gain topology, governed by a simple fuzzy logic controller, thus eliminating the requirement for intricate current and voltage equations for circuit elements. It makes the bidirectional energy flow possible and adopts a cost-effective, non-isolated configuration with a reduced count of semiconductor devices and passive components. The designed circuit was named ARVIN in honor of my 7-year-old son.
Keywords: SEPIC converter; Switched-inductor; Electrical vehicles (EVs); Grid; Vehicle-to-grid (V2G); Grid-to-vehicle (G2V) applications